Предмет: Алгебра,
автор: Мэри3331
(2+m)^2×(2-m)^2
(a-x)^2×(x+a)^2
решите плеееззз
Ответы
Автор ответа:
1
(2+m)^2×(2-m)^2=((2+m)*(2-m))^2=(4-m^2)^2=16-8m^2+m^4=m^4-8m^2+16
(a-x)^2×(x+a)^2=((a-x)*(x+a))^2=((a-x)*(a+x))^2=(a^2-x^2)^2=a^4-2a^2x^2+x^4
(a-x)^2×(x+a)^2=((a-x)*(x+a))^2=((a-x)*(a+x))^2=(a^2-x^2)^2=a^4-2a^2x^2+x^4
Похожие вопросы
Предмет: Физика,
автор: yanaromm887
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Математика,
автор: fsafarid010709
Предмет: История,
автор: MashaSudovtseva1504
Предмет: Алгебра,
автор: lol2113